1998
DOI: 10.1099/0022-1317-79-2-259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences between human immunodeficiency virus type 1 subpopulations in faeces and serum.

Abstract: To study human immunodeficiency virus type 1 (HIV-1) compartmentalization between intestine and blood, paired faecal and serum samples were collected from 204 HIV-1-infected persons. Direct sequencing of the gp120 V3 region obtained from 33 persons showed that faecal and serum sequences could be nearly homologous (0n3% different) or very dissimilar (11n3 % different). Individual clones were obtained and sequenced from the faecal and serum samples of 13 persons. In 6 persons the HIV-1 subpopulations in faeces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The performance of VIDISCA-454 in feces was investigated using broth suspensions from a sample-bank collected from HIV-1 infected individuals in 1994 and 1995 [8]. A norovirus infection was diagnosed in five people via real time RT-PCR [9], the viral load in feces suspension ranged between 5 × 10 3 and 3 × 10 7 genome copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of VIDISCA-454 in feces was investigated using broth suspensions from a sample-bank collected from HIV-1 infected individuals in 1994 and 1995 [8]. A norovirus infection was diagnosed in five people via real time RT-PCR [9], the viral load in feces suspension ranged between 5 × 10 3 and 3 × 10 7 genome copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…For example, different frequencies of antiviral resistant variants in gut mucosal biopsy samples with circulating virus in plasma were obtained from a minority of individuals (61). Similarly, V3 sequence differences were frequently found between variants of HIV recovered from feces and those found in peripheral blood (79,80).…”
Section: Fig 6 (A)mentioning
confidence: 99%
“…A number of other studies examining lymphoid and nonlymphoid tissue compartments have also suggested compartmentalization of viral evolution (9,15,20,21,22,30,51). Though there have been few studies of HIV-1 evolution in the intestinal mucosa, genotypic differences in the env, pro, and reverse transcriptase genes of HIV-1 quasispecies in the intestinal mucosa and blood have been described (35,43,44). HIV-1 isolates from the gastrointestinal mucosa have also been shown to differ from paired blood isolates in terms of their ability to induce cytopathology in infected cells and showed a greater sensitivity to serum neutralization in one study (4).…”
Section: Ccr5mentioning
confidence: 99%